Sizing agents comprising functionalized polyolefins
By coating the fibers with sizing agents containing functionalized polyolefin polymers, alkali compounds, non-ionic and ionic surfactants, the fiber fuzz and fracture problems during processing of fiber reinforced polymer composites are solved, and improved compatibility and adhesion between the fiber and the polymer matrix is achieved, and the mechanical properties of the composite are improved.
Patent Information
- Application Number
- CN202380064893.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-12
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-18
Smart Images

Figure BDA0005303744360000161 
Figure BDA0005303744360000171 
Figure BDA0005303744360000172
Abstract
Description
Technical Field
[0001] The present invention relates to sizing agents and the use of sizing agents as coatings on reinforcing fibers. The present invention also relates to sizing compositions comprising sizing agents. The present invention also relates to sized reinforcing fibers comprising reinforcing fibers coated with sizing agents, and methods for preparing sized reinforcing fibers. In addition, the present invention also relates to polymer composites comprising sized reinforcing fibers. Background Art
[0002] Fiber-reinforced polymer composites are generally used to prepare molded products, such as automobiles and aerospace parts, consumer goods and electrical components, which require such molded products to have the mechanical properties of a certain desired level, such as impact and tensile strength. Typically, such polymer composites have a polymer matrix in which fortifying fibers are dispersed. The possible factors of the mechanical properties of any composite material improvement are due to the effective transfer of load from matrix to fiber when composite material is subjected to a certain force. However, the degree of realizing the desired mechanical properties is at least partially governed by the degree of compatibility or adhesiveness between fortifying fibers and the polymer matrix. In addition, because fortifying fibers such as carbon fibers have low ductility and are usually brittle, fibers tend to produce fluff or fiber fractures during processing due to mechanical wear, which negatively affects the processability of fiber and the quality of the enhanced products.
[0003] One of the approaches to reduce fuzz and improve the interfacial compatibility between inorganic reinforcing fiber and organic polymer matrix is by coating reinforcing fiber with sizing agent.Usually, coating is the form of thin coating layer (typically ~ 100nm) referred to as sizing, which forms the interface between fiber and matrix.Therefore, the fiber through sizing has the improved compatibility and improved processability with the resin matrix in which fiber is dispersed.However, in some cases, reinforcing fiber may lose its tensile properties after sizing, which may negatively affect the subsequent processing and the processing of reinforcing fiber.
[0004] Various attempts have been made in the past to develop suitable sizing agents. For example, patent EP1403420B1 ("EP patent") claims a compound having at least one epoxy group per molecule, an anionic surfactant having ammonium ions as counterions, and a nonionic surfactant, wherein the nonionic surfactant (C) is contained at 1 / 50 to 1 / 2 (by weight) relative to the anionic surfactant (B). The EP patent points out that by restricting the weight ratio of the surfactant in this way, the reactivity of the ammonium ions relative to the epoxy group can be reduced, and as a result, changes over time can be significantly suppressed in the carbon fiber to which the sizing agent is adhered. Although the sizing agent described in the EP patent is promising, the teaching is limited to epoxy sizing agents that only use specific specific categories of anionic surfactants combined with nonionic surfactants in a specific ratio.
[0005] JP 635263 discloses a sizing agent for carbon fibers, which can impart sufficient strength to a carbon fiber composite material while suppressing the use of an emulsifier and an alkali material by using an easily emulsifiable acid-modified polyolefin. US2014 / 0227516 discloses a sizing agent for carbon fiber for reinforcing a thermoplastic matrix resin, the sizing agent substantially comprising a polymer component having a glass transition temperature of at least 20°C and exhibiting no endothermic peak indicating a melting endotherm of at least 3 J / g due to crystalline melting in a measurement using a differential scanning calorimeter; wherein the weight ratio of the polymer component constitutes 10 to 100 weight % of the non-volatile components of the sizing agent; wherein the polymer component is at least one component selected from the group consisting of an aromatic polyester resin, an aromatic polyester-polyurethane resin, and an amine-modified aromatic epoxy resin; wherein the aromatic polyester-polyurethane resin is a polymer prepared by addition polymerization of an aromatic polyester polyol and a polyisocyanate; wherein the amine-modified aromatic epoxy resin is a reaction product of an aromatic epoxy compound and an amine compound containing a hydroxyl group, and the ratio of the amine compound containing a hydroxyl group relative to the epoxy group of the aromatic epoxy compound is in the range of 1.0 to 2.0 molar equivalents.
[0006] US2012 / 0238688 discloses a carbon fiber reinforced resin composition comprising (A) a polyolefin resin, (B) an acid-modified polyolefin resin, and (C) a modified carbon fiber having an attachment amount of 0.2 to 5.0% by mass of a modified polyolefin resin containing an amino group, wherein the mass ratio of (A):(B) is 0:100 to 99.5:0.5, and the mass ratio of [(A)+(B)]:(C) is 40:60 to 97:3.
[0007] CN 106884330 discloses an emulsion-type sizing agent for carbon fiber, and a preparation method and application of the emulsion-type sizing agent. The method comprises the following steps: firstly, dissolving a polyurethane resin in an organic solvent that is volatile at room temperature, adding a surfactant, and mixing uniformly to obtain a main slurry solution; dispersing the surfactant in deionized water to obtain emulsified water; adding the emulsified water dropwise to the main slurry solution until the main slurry solution undergoes a phase inversion; finally, adding all the remaining emulsified water to the main slurry solution, and continuously stirring to obtain the final product. The final product does not solidify when it comes into contact with water, has a uniform particle size of 100-200nm, and has good stability; the emulsion-type sizing agent can be stored for 6 months under normal temperature and dry conditions; and has a heat-resistant temperature of up to 280-300°C.
[0008] Therefore, it is an object of the present invention to provide a sizing agent that imparts improved fiber-matrix compatibility in polymer composites. Another object of the present invention is to provide a sizing composition with improved emulsion stability. Another object of the present invention is to provide a sized reinforcing fiber with improved processability while maintaining desired mechanical properties. Summary of the invention
[0009] Therefore, one or more objects of the present invention are achieved by a sizing agent, the sizing agent comprising:
[0010] at least one functionalized polyolefin polymer,
[0011] ● At least one base compound, wherein the base compound is selected from the group consisting of:
[0012] i. Inorganic bases;
[0013] ii. an organic base; and
[0014] iii. any combination thereof;
[0015] ● at least one nonionic surfactant; and
[0016] - At least one ionic surfactant.
[0017] The total weight of the functionalized polyolefin polymer, the base compound, the nonionic surfactant and the ionic surfactant is 100 wt%. Preferably, the aqueous solution containing 0.01 wt% to 40.0 wt%, preferably 0.1 wt% to 30.0 wt%, preferably 0.1 wt% to 25.0 wt%, preferably 1.0 wt% to 10.0 wt%, preferably 1.0 wt% to 6.0 wt%, preferably 2.0 to 5.0 wt% of the sizing agent has a pH in the range of greater than 7.0 to 12.0, preferably 7.2 to 11.0, preferably 8.5 to 11.0, preferably 8.5 to 10.5.
[0018] Preferably, based on the total weight of the sizing agent, (a) the functionalized polyolefin polymer is present in an amount of 50.0 wt % to 90.0 wt %; (b) the nonionic surfactant is present in an amount of 10.0 wt % to 25.0 wt %; (c) the ionic surfactant is present in an amount of 0.5 wt % to 5.0 wt %; (d) the inorganic base, if present, is present in an amount of 1.0 wt % to less than 12.5 wt %; (e) the organic base, if present, is present in an amount of 8.0 wt % to 30.0 wt %; provided that the sizing agent comprises any one of the organic base or the inorganic base. The total weight of (a)-(e) is 100 wt %.
[0019] Preferably, based on the total weight of the sizing agent, (a) the functionalized polyolefin polymer is present in an amount of 55.0 wt % to 85.0 wt %; (b) the nonionic surfactant is present in an amount of 15.0 wt % to 25.0 wt %; (c) the ionic surfactant is present in an amount of 1.0 wt % to 3.0 wt %; (d) the inorganic base, if present, is present in an amount of 2.0 wt % to 10.0 wt %; (e) the organic base, if present, is present in an amount of 12.0 wt % to 18.0 wt %; provided that the sizing agent comprises any one of the organic base or the inorganic base. The total weight of (a)-(e) is 100 wt %.
[0020] Preferably, based on the total weight of the sizing agent, (a) the functionalized polyolefin polymer is present in an amount of 60.0 wt % to 75.0 wt %; (b) the nonionic surfactant is present in an amount of 15.0 wt % to 20.0 wt %; (c) the ionic surfactant is present in an amount of 1.0 wt % to 3.0 wt %; (d) the inorganic base, if present, is present in an amount of 2.0 wt % to 10.0 wt %; (e) the organic base, if present, is present in an amount of 12.0 wt % to 18.0 wt %; provided that the sizing agent comprises any one of the organic base or the inorganic base. The total weight of (a)-(e) is 100 wt %.
[0021] Preferably, based on the total weight of the sizing agent, (a) the functionalized polyolefin polymer is present in an amount of 65.0 wt % to 75.0 wt %; (b) the nonionic surfactant is present in an amount of 15.0 wt % to 20.0 wt %; (c) the ionic surfactant is present in an amount of 1.0 wt % to 3.0 wt %; (d) the inorganic base, if present, is present in an amount of 3.0 wt % to 8.0 wt %; (e) the organic base, if present, is present in an amount of 12.0 wt % to 18.0 wt %; provided that the sizing agent comprises any one of the organic base or the inorganic base. The total weight of (a)-(e) is 100 wt %.
[0022] Preferably, the sizing agent comprises an inorganic base or an organic base. Preferably, when the sizing agent comprises an inorganic base, the sizing agent does not contain an organic base. Preferably, when the sizing agent comprises an organic base, the sizing agent does not contain an inorganic base. Preferably, the sizing agent only comprises an inorganic base, and therefore preferably the sizing agent does not comprise, i.e. does not contain, an organic base.
[0023] The expression "sizing agent" as used throughout the present disclosure means a coating composition suitable for application on reinforcing fibers. The expression "(s)ized" as used throughout the present disclosure means reinforcing fibers coated with a sizing agent.
[0024] Advantageously, the present inventors have discovered that when reinforcing fibers are sized with the sizing agent of the present invention, not only do the reinforcing fibers maintain their mechanical properties, but also when such sized fibers are dispersed in a polymer matrix, the reinforcing fibers exhibit improved fiber-matrix compatibility.
[0025] Thus, in one aspect of the invention, the invention relates to the use of the sizing agent of the invention as a coating on at least a portion of the reinforcing fibers for improving the adhesion between the reinforcing fibers and a polymer matrix in which the reinforcing fibers are dispersed.
[0026] Functionalized polyolefin polymers
[0027] The sizing agent comprises at least one functionalized polyolefin. The expression "functionalized polyolefin polymer" means a polyolefin having one or more polar functional groups covalently connected to the polyolefin polymer. Alternatively, the expression "functionalized polyolefin polymer" may refer to a polyolefin copolymer in which an olefin monomer is copolymerized with one or more monomers having polar functional groups under pressure. The polar functional group may include a chemical group such as an anhydride group, an ester group, an epoxy group, an acyl group, a carboxylic acid group or an amide group.
[0028] The functionalized polyolefin polymer can be selected from the group consisting of maleic anhydride grafted polyolefins, maleic anhydride based polyolefin copolymers, maleic anhydride based polyolefin terpolymers, glycidyl (meth)acrylate based polyolefin copolymers, glycidyl (meth)acrylate grafted polyolefins, itaconic anhydride grafted polyolefins, citraconic anhydride grafted polyolefins, allyl succinic anhydride grafted polyolefins, and combinations thereof.
[0029] Preferably, the functionalized polyolefin polymer comprises or consists of a maleic anhydride grafted polyolefin. The maleic anhydride grafted polyolefin may be selected from the group consisting of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted copolymers of ethylene and propylene, maleic anhydride grafted copolymers of ethylene and an alpha-olefin having 4 to 10 carbon atoms, maleic anhydride grafted terpolymers of propylene-ethylene and an alpha-olefin having 4 to 10 carbon atoms, and any combination thereof.
[0030] Preferably, the functionalized polyolefin polymer is maleic anhydride grafted polypropylene.Maleic anhydride may be present in an amount of 0.01 wt% to 10.0 wt%, preferably 0.1 wt% to 7.0 wt%, preferably 0.1 wt% to 5.0 wt%, based on the total weight of the functionalized polyolefin polymer.
[0031] The functionalized polyolefin polymer may be present in an amount of 50.0 wt % to 90.0 wt %, based on the total weight of the sizing agent. Preferably, the functionalized polyolefin polymer is present in an amount of 55.0 wt % to 85.0 wt %, preferably 60.0 wt % to 80.0 wt %, preferably 60.0 wt % to 75.0 wt %, preferably 65.0 wt % to 75.0 wt %, preferably 60.0 wt % to 70.0 wt %, preferably 68.0 wt % to 75.0 wt %, preferably 62.0 wt % to 68.0 wt %, based on the total weight of the sizing agent.
[0032] Alkali compounds
[0033] The base compound is selected from an inorganic base or an organic base, or any combination thereof. Preferably, the base compound is selected from any one of an inorganic base or an organic base.
[0034] Preferably, the base compound is selected from any one of the following:
[0035] ● an inorganic base, based on the total weight of the sizing agent, present in an amount of 1.0 wt % to less than 12.5 wt %, preferably 1.0 wt % to less than 12.0 wt %, preferably 2.0 wt % to 10.0 wt %, preferably 3.0 wt % to 8.0 wt %; or
[0036] • The organic base is present in an amount of 8.0 to 30.0 wt. %, preferably 10.0 to 20.0 wt. %, preferably 12.0 to 18.0 wt. %, based on the total weight of the sizing agent.
[0037] Preferably, the sizing agent of the present invention comprises or consists of:
[0038] ● an inorganic base selected from the group consisting of potassium hydroxide, sodium hydroxide, cesium hydroxide, barium hydroxide, ammonium hydroxide and any combination thereof; and / or
[0039] ●An organic base selected from the group consisting of: N,N-dimethylaminoethanol (DMAE), 2-(methylamino)ethanol, 2-(ethylamino)ethanol, 2-(propylamino)ethanol, 2-(butylamino)ethanol, N-butyldiethanolamine, N-tert-butyldiethanolamine, triisopropanolamine, bis(2-hydroxypropyl)amine, N,N-bis(2-hydroxypropyl)ethanolamine, 1-[N,N-bis(2-hydroxyethyl)amino]-2-propanol, N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine, N,N,N′,N′-tetrakis(2-hydroxypropyl)ethylenediamine, morpholine, diethanolamine, diethylmethanolamine, N,N-dimethyl-dihydrosphingosine, and any combination thereof.
[0040] Preferably, the inorganic base comprises or consists of potassium hydroxide, and the organic base comprises or consists of N,N-dimethylaminoethanol (DMAE).
[0041] Nonionic surfactant
[0042] The nonionic surfactant may be selected from the group consisting of linear or branched alkylphenol ethoxylate, alkylphenol, polyoxyalkylene allylphenyl ether, octylphenoxypoly(ethyleneoxy)ethanol, sorbitan oleate, polyethylene glycol sorbitan monooleate, polyethylene glycol sorbitan monolaurate, tert-octylphenoxypolyethoxyethanol, polyoxyethylene (10) isooctylcyclohexyl ether, α-[3,5-dimethyl-1-(2-methylpropyl)hexyl]-ω-hydroxypolyoxy-1,2-ethanediyl, polyethylene glycol monoalkyl ether, and any combination thereof. Preferably, the nonionic surfactant is a linear or branched alkylphenol ethoxylate. Preferably, the linear or branched alkylphenol ethoxylate comprises or consists of branched polyoxyethylene (9) nonylphenyl ether.
[0043] Based on the total weight of the sizing agent, the nonionic surfactant may be present in an amount of 10.0 wt % to 25.0 wt %. Preferably, based on the total weight of the sizing agent, the nonionic surfactant is present in an amount of 10.0 wt % to 20.0 wt %, preferably in an amount of 15.0 wt % to 25.0 wt %, preferably in an amount of 15.0 wt % to 20.0 wt %.
[0044] Ionic surfactants
[0045] The ionic surfactant may comprise an alkali metal ion or an alkaline earth metal ion or an ammonium ion as a counter ion. Preferably, the ionic surfactant comprises an alkali metal ion.
[0046] The ionic surfactant can be selected from the group consisting of an alkali metal salt of dioctyl sulfosuccinate, an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid, an alkali metal salt of dicyclohexyl sulfosuccinate, an alkali metal salt of dihexyl sulfosuccinate, an alkali metal salt of dibutyl sulfosuccinate, an alkali metal salt of bis(2-ethylhexyl)sulfosuccinate, an alkali metal salt of dodecylbenzenesulfonic acid, an alkali metal salt of 4-dodecylbenzenesulfonic acid, an alkali metal salt of sulfosuccinic acid, an alkali metal salt of poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether, an alkali metal salt of dodecyl sulfate, sodium cholesterol sulfate, an alkali metal salt of deoxycholic acid, and any combination thereof.
[0047] Preferably, the ionic surfactant comprises or consists of an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid. Preferably, the alkali metal salt comprises or consists of a sodium salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid.
[0048] The ionic surfactant may be present in an amount of 0.5 to 5.0 wt %, preferably 1.0 to 3.0 wt %, based on the total weight of the sizing agent. The inventors surprisingly found that the use of an ionic surfactant does not result in any emulsion instability, since no gel formation was observed even when the sizing composition, once formed, was stored for more than one month.
[0049] The sizing agent may be formulated so that the weight ratio of nonionic surfactant to ionic surfactant is greater than 1.0. Preferably, the weight ratio of nonionic surfactant to ionic surfactant is from 2.0 to 50.0, preferably from 3.0 to 20.0.
[0050] Compound (A)
[0051] In one aspect of the present invention, the sizing agent may comprise at least one compound (A) selected from the group consisting of sodium metabisulfite, potassium metabisulfite, sodium hypochlorite, calcium hypochlorite, monochloramine, trichloroisocyanuric acid, sodium benzoate, 4-hexylresorcinol, chloroxylenol and any combination thereof. Preferably, based on the total weight of the sizing agent, at least one compound (A) is present in an amount of 0.1 wt % to 1.0 wt %, preferably 0.5 wt % to 1.0 wt %.
[0052] Sizing agent
[0053] The sizing agent of the present invention is formulated to include at least one functionalized polyolefin polymer, at least one base compound, at least one nonionic surfactant, at least one ionic surfactant and optionally at least one compound (A). The base compound can be combined with the functionalized polyolefin polymer, the nonionic surfactant and the ionic surfactant (each present in a specific ratio) to obtain the sizing agent of the present invention.
[0054] The sizing agent may comprise, based on the total weight of the sizing agent:
[0055] ● at least one functionalized polyolefin polymer present in an amount from 50.0 wt. % to 90.0 wt. %;
[0056] ● At least one base compound, wherein the base compound is selected from the group consisting of:
[0057] i. Inorganic bases;
[0058] ii. an organic base; and
[0059] iii. any combination thereof;
[0060] ● at least one nonionic surfactant present in an amount from 10.0 wt. % to 25.0 wt. %; and
[0061] ● at least one ionic surfactant present in an amount from 0.5% to 5.0% by weight;
[0062] wherein the inorganic base, if present, is present in an amount of 1.0 wt % to less than 12.5 wt % based on the total weight of the sizing agent, and wherein the organic base, if present, is present in an amount of 8.0 wt % to 30.0 wt % based on the total weight of the sizing agent.
[0063] The sizing agent may comprise, based on the total weight of the sizing agent,
[0064] ● a functionalized polyolefin polymer present in an amount of 50.0 wt % to 90.0 wt %, preferably 55.0 wt % to 85.0 wt %, preferably 60.0 wt % to 80.0 wt %, preferably 60.0 wt % to 75.0 wt %, preferably 65.0 wt % to 75.0 wt %, preferably 60.0 wt % to 70.0 wt %, preferably 68.0 wt % to 75.0 wt %;
[0065] ● a nonionic surfactant, which is present in an amount of 10.0 wt% to 25.0 wt%, preferably 10.0 wt% to 20.0 wt%, preferably 15.0 wt% to 25.0 wt%, preferably 15.0 wt% to 20.0 wt%; and
[0066] • An ionic surfactant, which is present in an amount of 0.5 to 5.0 wt%, preferably 1.0 to 3.0 wt%.
[0067] The proportion of the functionalized polyolefin polymer and the alkali compound can be adjusted to provide the desired emulsion stability. Preferably, when the alkali compound is an inorganic base, the weight ratio of the inorganic base present in the sizing agent to the functionalized polyolefin polymer is in the range of 0.01 to 0.24, preferably 0.04 to 0.12, preferably 0.06 to 0.1. Preferably, when the alkali compound is an organic base, the weight ratio of the organic base present in the sizing agent to the functionalized polyolefin polymer is in the range of 0.08 to 0.6, preferably 0.13 to 0.36, preferably 0.16 to 0.28.
[0068] Preferably, based on the total weight of the sizing agent, the sizing agent comprises:
[0069] ● a functionalized polyolefin polymer present in an amount of 50.0 wt % to 90.0 wt %, preferably 55.0 wt % to 85.0 wt %, preferably 60.0 wt % to 80.0 wt %, preferably 60.0 wt % to 75.0 wt %, preferably 65.0 wt % to 75.0 wt %, preferably 60.0 wt % to 70.0 wt %, preferably 68.0 wt % to 75.0 wt %;
[0070] A base compound, wherein the base compound is selected from any one of the following:
[0071] ● Inorganic base, which is 1.0 wt% to less than 12.5 wt%, preferably 1.0 wt%
[0072] to less than 12.0 wt %, preferably 2.0 wt % to 10.0 wt %, preferably 3.0 wt % to 8.0 wt %; or
[0073] ● An organic base, which is present in an amount of 8.0 to 30.0% by weight, preferably 10.0% by weight
[0074] to 20.0 wt %, preferably 12.0 wt % to 18.0 wt %;
[0075] ● a nonionic surfactant, which is present in an amount of 10.0 wt% to 25.0 wt%, preferably 10.0 wt% to 20.0 wt%, preferably 15.0 wt% to 25.0 wt%, preferably 15.0 wt% to 20.0 wt%; and
[0076] • An ionic surfactant, which is present in an amount of 0.5 to 5.0 wt%, preferably 1.0 to 3.0 wt%.
[0077] Sizing agents contain inorganic alkali
[0078] Preferably, the sizing agent comprises an inorganic base, and wherein, based on the total weight of the sizing agent:
[0079] The functionalized polyolefin polymer is present in an amount from 65.0 wt % to 75.0 wt %, preferably from 68.0 wt % to 75.0 wt %;
[0080] ● the inorganic base is present in an amount of 2.0 wt % to 10.0 wt %, preferably 3.0 wt % to 8.0 wt %;
[0081] ● nonionic surfactant is present in an amount of 10.0 wt% to 20.0 wt%, preferably 15.0 wt% to 20.0 wt%;
[0082] ● an ionic surfactant is present in an amount of 0.5 wt% to 5.0 wt%, preferably 1.0 wt% to 3.0 wt%; and
[0083] • Compound (A) is present in an amount of 0.1 to 1.0 wt%, preferably 0.1 to 0.8 wt%.
[0084] Preferably, the sizing agent comprises an inorganic base, and wherein, based on the total weight of the sizing agent:
[0085] The functionalized polyolefin polymer is maleic anhydride grafted polypropylene, present in an amount of 65.0 wt % to 75.0 wt %, preferably 68.0 wt % to 75.0 wt %;
[0086] The inorganic base is potassium hydroxide, present in an amount of 2.0 wt % to 10.0 wt %, preferably 3.0 wt % to 8.0 wt %;
[0087] ● The nonionic surfactant is branched polyoxyethylene (9) nonylphenyl ether, present in an amount of 10.0 wt % to 20.0 wt %, preferably 15.0 wt % to 20.0 wt %;
[0088] ● the ionic surfactant is an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid, present in an amount of 0.5 wt % to 5.0 wt %, preferably 1.0 wt % to 3.0 wt %; and
[0089] • Compound (A) is sodium metabisulfite, present in an amount of 0.1 wt% to 1.0 wt%, preferably 0.1 wt% to 0.8 wt%.
[0090] Sizing agents containing organic bases
[0091] Preferably, the sizing agent comprises an organic base, and wherein, based on the total weight of the sizing agent:
[0092] The functionalized polyolefin polymer is present in an amount of 60.0 wt % to 70.0 wt %, preferably 62.0 wt % to 68.0 wt %;
[0093] ● the organic base is present in an amount of 10.0 wt % to 20.0 wt %, preferably 12.0 wt % to 18.0 wt %;
[0094] ● nonionic surfactant is present in an amount of 10.0 wt% to 20.0 wt%, preferably 15.0 wt% to 20.0 wt%;
[0095] ● an ionic surfactant is present in an amount of 0.5 wt% to 5.0 wt%, preferably 1.0 wt% to 3.0 wt%; and
[0096] • Compound (A) is present in an amount of 0.1 to 1.0 wt%, preferably 0.1 to 0.8 wt%.
[0097] Preferably, the sizing agent comprises an organic base, and wherein, based on the total weight of the sizing agent:
[0098] The functionalized polyolefin polymer is maleic anhydride grafted polypropylene, present in an amount of 60.0 wt % to 70.0 wt %, preferably 62.0 wt % to 68.0 wt %;
[0099] The organic base is N,N-dimethylaminoethanol (DMAE), present in an amount of 10.0 wt % to 20.0 wt %, preferably 12.0 wt % to 18.0 wt %;
[0100] ● The nonionic surfactant is branched polyoxyethylene (9) nonylphenyl ether, present in an amount of 10.0 wt % to 20.0 wt %, preferably 15.0 wt % to 20.0 wt %;
[0101] ● the ionic surfactant is an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid, present in an amount of 0.5 wt % to 5.0 wt %, preferably 1.0 wt % to 3.0 wt %; and
[0102] • Compound (A) is sodium metabisulfite, present in an amount of 0.1 wt% to 1.0 wt%, preferably 0.1 wt% to 0.8 wt%.
[0103] Sizing composition
[0104] In some aspects of the invention, the present invention relates to a sizing composition comprising (i) a sizing agent according to the invention, and (ii) a dispersion medium, wherein the sizing composition has a pH greater than 7.0, preferably at least 7.2, preferably at least 8.5. Preferably, the sizing agent is dispersed in the dispersion medium. Preferably, the sizing composition is an emulsion having a sizing agent dispersed in the dispersion medium.
[0105] The sizing composition may have a pH in the range of greater than 7.0 to 12.0, preferably 7.2 to 11.0, preferably 8.5 to 11.0, preferably 8.5 to 10.5. The pH of the sizing composition may be controlled by using a suitable portion of a functionalized polyolefin polymer and an alkaline compound. The inventors have found that suitable control of pH imparts desired emulsion stability to the sizing composition and affects the properties and performance of the sizing agent.
[0106] Preferably, when the alkaline compound is an organic base, the pH of the sizing composition is maintained in the range of 8.5 to 10.5. Alternatively, preferably, when the alkaline compound is an inorganic base, the pH of the sizing composition is maintained in the range of 7.2 to 8.5.
[0107] The dispersion medium can be a protic solvent. Non-limiting examples of protic solvents include aqueous solvents or at least one organic alcohol having 1 to 20 carbon atoms. Preferably, at least one organic alcohol is selected from methanol, ethanol, n-propanol, isopropanol, n-butanol, amyl alcohol, hexanol, cyclohexanol, benzyl alcohol and decanol.
[0108] Preferably, the dispersion medium is an aqueous solvent.Preferably, the sizing composition comprises a sizing agent as disclosed herein and a dispersion medium comprising an aqueous solvent, wherein the pH of the sizing composition has a pH greater than 7.0.
[0109] The aqueous solvent may comprise water and a water miscible solvent. The water miscible solvent may be selected from methanol, ethanol, n-propanol, isopropanol, dioxane, tetrahydrofuran, acetone, acetonitrile and combinations thereof. The volume ratio of water:water miscible solvent may vary from 99:1 to 10:90, or from 99:1 to 50:50, or from 99:1 to 70:30. Preferably, the aqueous solvent comprises water completely, preferably deionized water.
[0110] The sizing agent may be present in an amount of 0.01 wt % to 40.0 wt %, preferably 0.1 wt % to 30.0 wt %, preferably 0.1 wt % to 25.0 wt %, preferably 1.0 wt % to 10.0 wt %, preferably 1.0 wt % to 6.0 wt %, preferably 2.0 to 5.0 wt %, based on the total weight of the sizing composition.
[0111] Based on the total weight of the sizing composition, the dispersion medium can be present in an amount of 60.0 wt % to 99.99 wt %, preferably 70.0 wt % to 99.9 wt %, preferably 75.0 wt % to 99.9 wt %, preferably 90.0 wt % to 99.0 wt %, preferably 94.0 wt % to 99.0 wt %, preferably 95.0 to 98.0 wt %.
[0112] Preferably, before sizing the reinforcing fibers, the sizing composition is further diluted with a dispersion medium to provide a desired sizing content on the reinforcing fibers. Preferably, based on the total weight of the sizing composition, the sizing agent is present in an amount of 1.0 wt % to 6.0 wt %, preferably 1.0 wt % to 5.0 wt %, and the dispersion medium is present in an amount of 94.0 wt % to 99.0 wt %, preferably 95.0 wt % to 99.0 wt %.
[0113] The sizing composition can be in the form of a solution, dispersion or emulsion in a solvent. Preferably, the sizing composition is in the form of an emulsion, wherein the functionalized polyolefin polymer is emulsified at a temperature higher than the melting point of the functionalized polyolefin polymer, and stabilized with a suitable combination of ionic and nonionic surfactants. The inventors surprisingly found that even when an alkali metal-based ionic surfactant is used to prepare a sizing agent, desired emulsion stability is achieved.
[0114] Preparation of sizing composition
[0115] The sizing composition can be prepared by introducing the sizing agent according to the present invention into a reactor vessel containing a suitable dispersion medium such as water. Thereafter, the reactor can be purged with an inert gas such as nitrogen, and the reaction mixture can be stirred or agitated at about 700-950 rpm and at any temperature of 150° C. to 175° C. After about 1 or 2 hours of completion, the reactor vessel can be cooled for about 1 hour, after which the sizing composition can be recovered from the reactor vessel.
[0116] Preferably, when the sizing composition is a water-based emulsion, each of the components constituting the sizing agent can be added to water in a beaded state under agitation and then heat treated. The agitation step can be carried out in a homogenizer, a mixer or a ball ground with mechanical shearing, and emulsified by phase inversion by gradually adding water.
[0117] Sized reinforcement fibers
[0118] In some aspects of the invention, the present invention relates to sized reinforcing fibers. The sized reinforcing fibers may include reinforcing fibers selected from the group consisting of carbon fibers, basalt fibers, glass fibers, polymer fibers and metal fibers, and wherein at least a portion of the reinforcing fibers is provided with a sizing agent according to the present invention. The expression "at least a portion" means at least 50%, preferably at least 60%, preferably at least 90%, preferably at least 100% of the outer surface of the reinforcing fibers.
[0119] Preferably, the reinforcing fiber is a carbon fiber. The carbon fiber can include graphite, expanded graphite, graphene, pyrolytic carbon fiber, carbon nanotubes, graphitized carbon black and combinations thereof. The carbon fiber can be in the form of a tow, knitted or woven, or in the form of a woven or nonwoven mat. The fiber can be continuous or chopped. The size of the fiber can be in the form of chopped fibers cut into 1-15 mm long for the manufacture of fiber-reinforced composite materials.
[0120] Preferably, at least a portion of the reinforcing fiber is coated or sized with a sizing agent according to the present invention. Preferably, the entire surface of the reinforcing fiber is coated or sized with a sizing agent according to the present invention. Based on the weight of the reinforcing fiber through sizing, the sizing agent can be present in an amount of 0.01 wt % to 3.0 wt %, preferably 0.05 wt % to 1.5 wt %, preferably 0.1 wt % to 1.2 wt %.
[0121] As demonstrated by the experimental results provided in this disclosure, when reinforcing fibers are sized with the sizing agent of the present invention, the reinforcing fibers are able to maintain or even improve their tensile properties. This is particularly advantageous because the sized fibers can be used to prepare polymer composites with desired mechanical properties.
[0122] Method for preparing sized reinforcing fibers
[0123] In one aspect of the present invention, the present invention relates to a method for producing a sized reinforcing fiber according to the present invention. The method for producing a sized reinforcing fiber may comprise the following steps:
[0124] ● providing a reinforcing fiber according to the present invention, preferably wherein the reinforcing fiber is a carbon fiber;
[0125] ● contacting the reinforcing fibers with a sizing composition according to the invention and obtaining precursor sized reinforcing fibers; and
[0126] • Drying the precursor sized reinforcement fibers to obtain sized reinforcement fibers.
[0127] The step of contacting the reinforcing fibers may include any of spraying the reinforcing fibers with the sizing composition or dipping the reinforcing fibers in the sizing composition, or immersing the reinforcing fibers in a sizing bath containing the sizing composition.
[0128] In some aspects of the invention, the step of "contacting the reinforcing fibers with the sizing composition" includes pulling the reinforcing fibers through a sizing bath containing the sizing composition, and thereafter forming the step of sizing the reinforcing fibers. The pulling of the reinforcing fibers may include pulling the reinforcing fibers through the sizing bath using a roller. Pulling the reinforcing fibers with a roller is particularly preferred because it allows the sizing on the reinforcing fibers to be evenly applied.
[0129] Preferably, the method for applying the sizing composition may comprise the following steps: by downstream winder, fortifying fiber is pulled out from creel, fortifying fiber is made to make fiber sizing by sizing bath, then subsequently by dryer, for example, the heated pipe with one or more temperature controlled regions, and then the fortifying fiber through sizing is wound onto reel. Drying step can be carried out by heating at a suitable temperature and heating a suitable time period sufficient to remove any water or any trace solvent (dispersion medium).
[0130] The drying process may include passing the precursor sized reinforcement fibers through one or more heating zones operating at any temperature from about 50° C. to about 90° C. for a period of about 0.5 to 2.0 minutes. Alternatively, the drying step may be performed by drying the precursor sized reinforcement fibers at ambient room temperature (~19° C.-32° C.) for a period of time ranging from about 20 hours to 72 hours.
[0131] Polymer composites
[0132] In one aspect of the present invention, the present invention relates to a polymer composite material comprising:
[0133] a polymer matrix comprising a polyolefin polymer, preferably the polyolefin polymer is selected from polypropylene or polyethylene, more preferably the polyolefin polymer is polypropylene; and
[0134] - One or more sized reinforcing fibers according to the present invention, wherein the one or more sized reinforcing fibers are dispersed in a polymer matrix. Preferably, the one or more sized reinforcing fibers are sized carbon fibers.
[0135] Preferably, the polymer composite is carbon fiber reinforced polypropylene. Polypropylene can include polypropylene homopolymers, preferably isotactic polypropylene (iPP). Alternatively, polypropylene can be a propylene-ethylene random copolymer (random PP) or a heterophasic polypropylene. Polyethylene can be a copolymer derived from ethylene and one or more alpha-olefins with 4 to 10 carbon atoms, preferably an alpha-olefin with 6 or 8 carbon atoms.
[0136] The inventor surprisingly found that when the sized reinforcing fibers are dispersed in a polymer matrix, the sized reinforcing fibers can show the desired adhesion to the polymer matrix. A suitable index for measuring the degree of adhesion between the sized reinforcing fibers and the polymer matrix is by measuring the apparent interfacial shear strength between the sized fibers and the polymer matrix.
[0137] Therefore, the higher the apparent interfacial shear strength, the higher the degree of adhesion or compatibility between the sized reinforcing fibers and the polymer matrix.One of the tests used to determine the apparent interfacial shear strength is the Micromechanical Single-Fibre Pull-Out Test according to DIN SPEC 19289.
[0138] The polymer composite material can be manufactured by any known method for preparing the polymer composite material, such as melt compounding or solution processing. Under solution processing, the reinforcing fiber can be impregnated with a solution comprising a polymer, and the solvent can be removed subsequently. A solution suitable for dissolving the polymer but not suitable for dissolving the sizing agent can be selected.
[0139] Alternatively, when the manufacturing method includes melt compounding, the polymer and the fortifying fiber are blended in a high-speed mixer or by manual mixing. After this, the blend can be fed into the throat of the extruder via a hopper. Alternatively, the fortifying fiber can be directly fed into the extruder in the throat and / or downstream by a side line filler or by being compounded into a masterbatch with the desired polymer and fed into the extruder, and the fortifying fiber is introduced into the polymer. After this, the composition can be extruded to provide an extrudate with a desired shape. Alternatively, the extrudate can be immediately quenched and granulated in a water bath. Such pellets can be used for subsequent molding, shaping, for various industrial applications.
[0140] In one aspect of the invention, the invention relates to articles formed from the polymer composite material according to the invention. The articles may be automotive parts, battery housings and trays, consumer goods, electronic and medical devices.
[0141] The invention will now be further illustrated based on the following non-limiting examples. Example
[0142] Material: For the purposes of the examples, the following materials were used:
[0143] Table 1
[0144]
[0145]
[0146] Test plan: The following testing protocols and standards were followed:
[0147] Table 2
[0148]
[0149] Three sizing agent samples (IE1-IE3) according to the present invention were formulated and the corresponding sizing compositions were prepared. Thereafter, the sizing compositions were used to prepare sized carbon fibers. The performance of the sizing agents (IE1-IE3) was evaluated for a baseline sizing agent (BSA) and for unsized carbon fibers.
[0150] The following sizing agent samples were prepared:
[0151] Table 3
[0152]
[0153] Preparation of sizing composition
[0154] By adding sizing agent to deionized water, then mixing and emulsifying to prepare sizing composition. The concentration of sizing agent in the obtained sizing composition is provided in Table 4 below. In particular, the method follows the following steps: the sizing agent comprising functionalized polyolefin polymer (maleic anhydride grafted polyolefin), alkali compound, nonionic surfactant (branched polyoxyethylene (9) nonylphenyl ether), ionic surfactant (AEROSOL OT 70PG) and compound A (sodium pyrosulfite) is introduced into the reactor container containing deionized water, after which the reactor is purged with nitrogen and a mixture is obtained. Thereafter, the mixture is stirred at a temperature of 175 ° C with 850rpm. After completing heating at 175 ° C for about 1 hour, the reactor is cooled and the sizing composition is recovered. Each of sizing agents (IE1-IE3) and benchmark sizing agents (BSA) is followed to obtain the sizing composition. Each of the sizing compositions is in the form of an emulsified aqueous dispersion.
[0155] For each of the sizing compositions, the pH of the sizing composition was determined at room temperature using a pH meter. From Table 4, it is observed that the commercial benchmark sizing agent (BSA) is acidic in nature, while sizing compositions IE2 and IE3 are alkaline in nature. Sizing composition IE1 has a pH close to 12, indicating a strong alkaline nature of the sizing composition.
[0156] Table 4
[0157]
[0158] Preparation of sized carbon fibers
[0159] Each of the sizing agents IE1-IE3 thus obtained is further diluted with deionized water and used to size the bundle of unsized carbon fibers. The concentration of the sizing agent before and after dilution in the sizing composition is provided in Table 4. The method for preparing sized carbon fibers includes the step of pulling the unsized carbon fiber bundle through a sizing bath containing the prepared sizing composition. The unsized carbon fiber bundle can be pulled at a speed of 0.8 to 1.0 m / min using a tension of 1.0 to 1.2 bar.
[0160] Excess sizing agent was squeezed out by means of counter-rotating rollers. The coated carbon fibers were dried in a circulating air drying oven at 120° C. for 3 h to finally prepare samples for further evaluation. For each of the obtained sized carbon fibers, the sizing content on the obtained sized carbon fibers was about 1.0-1.1% by weight based on the total weight of the sized carbon fibers.
[0161] The mechanical properties of the resulting sized carbon fibers were thereafter evaluated using single fiber tensile measurements, as provided below:
[0162] Table 5
[0163] Tensile strength(MPa) Tensile modulus(GPa) Unsized carbon fiber ~3227 ~270 Carbon fiber sized with a baseline sizing agent ~3334 ~260 Carbon fiber sized with sizing agent (IE1) ~3393 ~271 Carbon fiber sized with sizing agent (IE2) ~3496 ~272 Carbon fiber sized with sizing agent (IE3) ~3520 ~266
[0164] Micromechanical single fiber pullout testing: The apparent interfacial shear strength measurement was used to determine the degree of compatibility between the sized carbon fibers and the polypropylene matrix using a single fiber pull-out test. The prepared sized carbon fibers were used to evaluate the interfacial shear strength by following the method described in DIN SPEC 19289. Four different samples were prepared using sized carbon fibers obtained from each of the IE1-IE3 sizing agents and the baseline sizing agent.
[0165] By embedding each of the sized carbon fibers in a molten polypropylene matrix ( The sample was prepared in a molten polypropylene (PP595A). The sample holder containing the polymer matrix was transferred to the embedding device. A single fiber of 1 mm in length was embedded into the molten polypropylene polymer matrix by a computer-controlled program. The embedding process was assisted by a dual camera system to be able to place and observe the fiber into the molten polymer matrix. The fiber was embedded at a constant speed.
[0166] The actual embedding length was measured after the pull-out test on an optical microscope. Subsequently, pull-out tests were carried out under quasi-static load conditions (QSFPO) with a pull-out speed of 0.001 mm / s and under dynamic load (DSFPO) of 10 mm / s. During the tests, the force-displacement curve was recorded in the case of QSFPO. At least 15 specimens were tested for each fiber type to ensure a meaningful statistical evaluation. The apparent interfacial shear strength was determined from the force-displacement curve.
[0167] The results are provided in the following table:
[0168] Table 6
[0169]
[0170] Results and Conclusions: For the sizing compositions prepared with sizing agents IE1-IE3, no gel formation was observed even after 30 days, indicating that the sizing compositions had desirable emulsion stability.
[0171] From the data provided in Table 5, the inventors concluded that the mechanical properties of the sized carbon fibers prepared from sizing agents IE1-IE3 were retained, and in some cases even further improved, compared to the unsized carbon fibers. For example, in all cases, the sized carbon fibers prepared from sizing agents (IE1-IE3) had higher tensile strength than the initial unsized carbon fibers.
[0172] Furthermore, from Table 5, the inventors concluded that the sized carbon fibers prepared from sizing agents IE1-IE3 had higher tensile strength than the sized carbon fibers prepared from the commercially purchased benchmark sizing agent (BSA).
[0173] From the data provided in Table 6, the inventors concluded that the sized carbon fibers prepared from sizing agents IE2 and IE3 exhibited high fiber-matrix adhesion, indicating excellent compatibility between the fibers and the polymer matrix.
[0174] In fact, polypropylene composites prepared from sized carbon fibers with IE3 as sizing agent have higher adhesion to the polypropylene matrix than even carbon fibers sized with the benchmark sizing agent (BSA). The adhesion or compatibility of carbon fibers prepared with sizing agent IE2 to the polypropylene matrix is similar to that of carbon fibers sized with the benchmark sizing agent (BSA). From the results provided in Table 6, the inventors conclude that the appropriate choice of sizing agent and corresponding sizing composition affects the properties of the sized carbon fibers in terms of compatibility with the polymer matrix.
[0175] Furthermore, no fiber breakage or fuzz formation was observed from the single fiber pullout test, indicating that sizing agents IE1-IE3 imparted the desired protective coating on the carbon fiber surface.
Claims
1. A sizing agent comprising: ●at least one functionalized polyolefin polymer; ● At least one base compound, wherein the base compound is selected from the group consisting of: i. Inorganic bases; ii. an organic base; and iii. any combination thereof; ● at least one nonionic surfactant; and - At least one ionic surfactant.
2. The sizing agent according to claim 1, wherein the alkaline compound is selected from any one of the following: The inorganic base is present in an amount of 1.0 wt % to less than 12.5 wt %, preferably 2.0 wt % to 10.0 wt %, more preferably 3.0 wt % to 8.0 wt %, based on the total weight of the sizing agent; or The organic base is present in an amount of 8.0 to 30.0 wt %, preferably 10.0 to 20.0 wt %, more preferably 12.0 to 18.0 wt %, based on the total weight of the sizing agent.
3. The sizing agent according to claim 1-2, wherein based on the total weight of the sizing agent: The functionalized polyolefin polymer is present in an amount from 50.0 wt % to 90.0 wt %; • the nonionic surfactant is present in an amount of 10.0 wt% to 25.0 wt%; and • the ionic surfactant is present in an amount of 0.5 wt% to 5.0 wt%.
4. The sizing agent of claims 1-3, wherein the functionalized polyolefin polymer is selected from the group consisting of maleic anhydride grafted polyolefins, maleic anhydride based polyolefin copolymers, maleic anhydride based polyolefin terpolymers, (meth) acrylate glycidyl based polyolefin copolymers, (meth) acrylate glycidyl grafted polyolefins, itaconic anhydride grafted polyolefins, citraconic anhydride grafted polyolefins, allyl succinic anhydride grafted polyolefins, and combinations thereof.
5. The sizing agent according to any one of claims 1 to 4, wherein ● the inorganic base is selected from the group consisting of potassium hydroxide, sodium hydroxide, cesium hydroxide, barium hydroxide, ammonium hydroxide and any combination thereof; and / or ●The organic base is selected from the group consisting of: N,N-dimethylaminoethanol (DMAE), 2-(methylamino)ethanol, 2-(ethylamino)ethanol, 2-(propylamino)ethanol, 2-(butylamino)ethanol, N-butyldiethanolamine, N-tert-butyldiethanolamine, triisopropanolamine, bis(2-hydroxypropyl)amine, N,N-bis(2-hydroxypropyl)ethanolamine, 1-[N,N-bis(2-hydroxyethyl)amino]-2-propanol, N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine, N,N,N′,N′-tetrakis(2-hydroxypropyl)ethylenediamine, morpholine, diethanolamine, diethylmethanolamine, N,N-dimethyl-dihydrosphingosine and any combination thereof.
6. The sizing agent according to any one of claims 1 to 5, wherein the nonionic surfactant is selected from the group consisting of linear or branched alkylphenol ethoxylates, alkylphenols, polyoxyalkylene allylphenyl ethers, octylphenoxypoly(ethyleneoxy)ethanol, sorbitan oleate, polyethylene glycol sorbitan monooleate, polyethylene glycol sorbitan monolaurate, tert-octylphenoxypolyethoxyethanol, polyoxyethylene (10) isooctylcyclohexyl ether, α-[3,5-dimethyl-1-(2-methylpropyl)hexyl]-ω-hydroxypolyoxy-1,2-ethanediyl, polyethylene glycol monoalkyl ethers, and any combination thereof.
7. The sizing agent according to any one of claims 1 to 6, wherein the ionic surfactant is selected from the group consisting of an alkali metal salt of dioctyl sulfosuccinate, an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid, an alkali metal salt of dicyclohexyl sulfosuccinate, an alkali metal salt of dihexyl sulfosuccinate, an alkali metal salt of dibutyl sulfosuccinate, an alkali metal salt of bis(2-ethylhexyl)sulfosuccinate, an alkali metal salt of dodecylbenzenesulfonic acid, an alkali metal salt of 4-dodecylbenzenesulfonic acid, an alkali metal salt of sulfosuccinic acid, an alkali metal salt of poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether, an alkali metal salt of dodecyl sulfate, sodium cholesterol sulfate, an alkali metal salt of deoxycholic acid, and any combination thereof.
8. The sizing agent according to any one of claims 1 to 7, wherein the sizing agent further comprises at least one compound (A) selected from the group consisting of sodium metabisulfite, potassium metabisulfite, sodium hypochlorite, calcium hypochlorite, monochloramine, trichloroisocyanuric acid, sodium benzoate, 4-hexylresorcinol, chloroxylenol and any combination thereof, preferably wherein the at least one compound (A) is present in an amount of 0.1 wt % to 1.0 wt % based on the total weight of the sizing agent.
9. The sizing agent according to any one of claims 1 to 8, wherein the alkaline compound is an inorganic base and wherein based on the total weight of the sizing agent: The functionalized polyolefin polymer is maleic anhydride grafted polypropylene, which is present in an amount of 65.0 wt% to 75.0 wt%; The inorganic base is potassium hydroxide, which is present in an amount of 2.0 wt % to 10.0 wt %; The nonionic surfactant is branched polyoxyethylene (9) nonylphenyl ether, which is present in an amount of 10.0 wt % to 20.0 wt %; The ionic surfactant is an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid, which is present in an amount of 0.5 wt % to 5.0 wt %; and The compound (A) is sodium metabisulfite, which is present in an amount of 0.1 wt% to 1.0 wt%.
10. The sizing agent according to any one of claims 1 to 8, wherein the alkaline compound is an organic base and wherein based on the total weight of the sizing agent: The functionalized polyolefin polymer is maleic anhydride grafted polypropylene, which is present in an amount of 60.0 wt% to 70.0 wt%; The organic base is N,N-dimethylaminoethanol (DMAE), which is present in an amount of 10.0 wt % to 20.0 wt %; The nonionic surfactant is polyoxyethylene (9) nonylphenyl ether, which is present in an amount of 10.0 wt % to 20.0 wt %; The ionic surfactant is an alkali metal salt of 1,4-bis[(2-ethylhexyl)oxy]-1,4-dioxo-2-butanesulfonic acid, which is present in an amount of 0.5 wt % to 5.0 wt %; and The compound (A) is sodium metabisulfite, which is present in an amount of 0.1 wt% to 1.0 wt%.
11. A sizing composition comprising (i) a sizing agent according to any one of claims 1 to 10, and (ii) a dispersion medium, wherein the sizing composition has a pH greater than 7.
0.
12. Sized reinforcing fibers, comprising reinforcing fibers selected from the group consisting of carbon fibers, basalt fibers, glass fibers, polymer fibers and metal fibers, preferably the reinforcing fibers are carbon fibers, and wherein at least a portion of the reinforcing fibers are provided with a sizing agent according to any one of claims 1 to 10.
13. A method for producing a sized reinforcing fiber according to claim 12, comprising the steps of: ● Providing a reinforcing fiber according to claim 12, preferably wherein the reinforcing fiber is a carbon fiber; ● contacting the reinforcing fiber with the sizing composition according to claim 11 and obtaining a precursor sized reinforcing fiber; and • Drying the precursor sized reinforcement fibers to obtain the sized reinforcement fibers.
14. A polymer composite material comprising: a polymer matrix comprising a polyolefin polymer, preferably the polyolefin polymer is selected from polypropylene or polyethylene, more preferably the polyolefin polymer is polypropylene; and ● One or more sized reinforcing fibers according to claim 12, preferably one or more sized reinforcing fibers according to claim 12 are sized carbon fibers, wherein the one or more sized reinforcing fibers are dispersed in the polymer matrix.
15. Use of a sizing agent according to any one of claims 1 to 10 as a coating on at least a portion of reinforcing fibers for improving the adhesion between the reinforcing fibers and a polymer matrix in which the reinforcing fibers are dispersed.
Citation Information
Patent Citations
Sizing agent for carbon fiber, aqeous dispersion thereof; carbon fiber treated by sizing; sheet;form object comprising the carbon fiber; and carbon fiber;reinforced composite material
EP1403420B1
Examination of blood
JP1988005263A
Carbon fiber-reinforced resin composition
US20120238688A1
Carbon fiber sizing agent, carbon fiber strand, and fiber-reinforced composite
US20140227516A1